A randomized controlled trial combining house screening and insecticide-treated nets reduces malaria transmission in northwestern Ethiopia - Aklilu K. Belay; Abebe Asale; Catherine L. Sole; Abdullahi A. Yusuf; Baldwyn Torto; Zewdu Abro; Menale Kassie; Clifford M. Mutero; David P. Tchouassi (Scientific Reports)
Abstract House screening (HS) of doors, eaves, and windows using wire-mesh has demonstrated potential in the integrated vector management of malaria. However, limited epidemiological data are available to guide its implementation across different ecological settings. In a 16-month randomized controlled trial (follow-up period) conducted across three agroecological areas (dry mountain, plateau highland, and semi-arid) in Jabi Tehnan district, northwestern Ethiopia, treatment houses were equipped with HS combined with insecticide-treated nets (ITNs), while control houses received ITNs only. The intervention led to a significant 2.3-fold reduction in indoor malaria vector density, the primary entomologic outcome, largely influenced by An. gambiae s.l. mosquitoes. Fewer blood-fed mosquitoes were found in screened houses, indicating reduced human bites, which translated to six-fold decline in malaria prevalence (0.7%), the primary epidemiologic outcome, compared to control houses (4.3%). In contrast, Plasmodium sporozoite infection rates showed no differences between screened and control houses or agroecological zones, with An. arabiensis and An. funestus s.l. identified as the primary vectors. A modest protective effectiveness (22.6%) was observed, based on the estimated entomological inoculation rate of 0.24 and 0.31 infectious bites/person/night in screened and control houses, respectively, with no variation by agroecology. Despite the synergistic impact of HS with existing ITNs in reducing vector densities, human bite rates, and household malaria prevalence, sustained transmission persisted, partly due to the presence of highly competent vectors such as An. funestus s.l. which had an overall sporozoite rate of 68%. Future research should explore the interactions between vector behavioral adaptations, ecological and social factors contributing to residual transmission, even with seemingly effective control measures.